Modernism and Fascism - Griffin, R. author. aut Link
XV, 470 p.
Keywords: Intellectual debates surrounding modernity, modernism and fascism continue to be active and hotly contested. In this ambitious book, renowned expert on fascism Roger Griffin analyzes Western modernity and the regimes of Mussolini and Hitler and offers a pioneering new interpretation of the links between these apparently contradictory phenomena.